Correlation of Prediabetes and Metabolic Syndrome in Rural Population of Dinanath - Arif Gulzar, Nasir Rashid, M Faheem Siddiqi, Zoya Arif, Riasat Ali, Muhammad Aleem Uddin (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: The prediabetes in the age group of 20-35 with minor ailments were found in patients attending OPD of medical department in pak red crescent medical college Dina nath. the association of prediabetes with other risk factors of metabolic syndrome were found. Materials and Methods: Forty two patients including 24 males and 18 females were selected with minor ailments and the other associated risk factors of metabolic syndrome were investigated. Results: Were framed in tables the prevalence of metabolic syndrome was found in 78% of cases with prediabetes as compared to 22% without this syndrome. Conclusion: The patients with prediabetes should be evaluated for other risk factors of metabolic syndrome so as to avoid the serious complications of the other risk factors.